Analisis Business Model Canvas Pada Pt. Duta Merpati Pusat - Zayyan Fayi Alif (Jurnal Mirai Management, 2023)
One of the largest wholeseller suppliers of iron, steel, and stainless steel, PT Duta Merpati Indonesia has several branches in Indonesia. The goal of this study is to figure out the current business strategy, look at the strengths and weaknesses of the business processes, and make suggestions for using the Business Model Canvas to improve distribution skills at PT Duta Merpati Pusat. The composing strategy utilized in this last venture research is Subjective technique. The examination results are accentuated on giving an objective depiction of the genuine condition of the article under study. The unit of examination in this exploration is PT Duta Merpati Pusat. The business improvement technique that is appropriate for execution at PT. Duta Merpati Pusat in light of the examination that has been done is basically a client relationship with the execution of a peddling procedure or direct showcasing to increment deals and acquaint items with new clients, as well as a Key association that is exceptionally useful in business improvement, what's more, PT. Duta Merpati Pusat has an offer that is more in item quality and more adaptable limits Keywords: Business, model, canvas, Duta Merpati